Business Development Strategy of Seblak Putri Setu During The COVID-19 Pandemic - Hermawan, Yudan; Tamaris, Titania (Universitas Negeri Padang, 2022)
This study aims to describe the business development strategy carried out by Seblak Putri Setu during the Covid-19 pandemic. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out by observation and interviews. Data analysis was carried out with an interactive model that included data collection, data reduction, data presentation and drawing conclusions. The results showed that several business development strategies were carried out by Seblak Putri Setu, namely expanding dining areas, adding decorations in the dining area, innovating new menus to adjusting patterns of changing consumer behavior by partnering and conducting online promotions and providing services for non-cash payments.